2015
DOI: 10.1021/es505649d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of Nalidixic Acid by Nano-magnetite via Fe2+/O2-Mediated Reactions

Abstract: Organic pollution has become a critical issue worldwide due to the increasing input and persistence of organic compounds in the environment. Iron minerals are potentially able to degrade efficiently organic pollutants sorbed to their surfaces via oxidative or reductive transformation processes. Here, we explored the oxidative capacity of nano-magnetite (Fe3O4) having ∼ 12 nm particle size, to promote heterogeneous Fenton-like reactions for the removal of nalidixic acid (NAL), a recalcitrant quinolone antibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 71 publications
1
49
0
Order By: Relevance
“…The reason should be related to the degradation of ciprofloxacin in these two systems, besides surface adsorption. Both iron sulfide and magnetite have been reported to be capable for activating dissolved O 2 in water, which results in the production of hydroxyl radicals (·OH) that are highly reactive for oxidative degradation of organic compounds [42][43][44]. For validating such a guess, the removal of ciprofloxacin by FeS/Fe 3 O 4 or FeS/Fe 3 O 4 @BC500 alone was conducted under nitrogen atmosphere.…”
Section: Comparison Of Various Catalysis Systems For Removal Of Cipromentioning
confidence: 99%
“…The reason should be related to the degradation of ciprofloxacin in these two systems, besides surface adsorption. Both iron sulfide and magnetite have been reported to be capable for activating dissolved O 2 in water, which results in the production of hydroxyl radicals (·OH) that are highly reactive for oxidative degradation of organic compounds [42][43][44]. For validating such a guess, the removal of ciprofloxacin by FeS/Fe 3 O 4 or FeS/Fe 3 O 4 @BC500 alone was conducted under nitrogen atmosphere.…”
Section: Comparison Of Various Catalysis Systems For Removal Of Cipromentioning
confidence: 99%
“…MNPs (∼12 nm) show good oxidative capacity to promote heterogeneous Fenton-like reactions for the removal of nalidixic acid (NAL), a recalcitrant quinolone antibacterial agent. It is suggested that oxidative degradation of adsorbed NAL is by reactive oxygen species (ROS) produced via oxidation of both dissolved and structural Fe 2+ ions [198]. Functionalized MNPs in alginate beads is used in the advanced Fenton oxidation of a malodorous compound (3 methyl-indole: 3-MI) without significant leaching of iron [199].…”
Section: Activation Of Oxidants For Organic Contaminants Degradationmentioning
confidence: 99%
“…In their fine particle form they have also attracted a great deal of recent interest in biomedical applications ranging from magnetic actuation for drug delivery, magnetic hyperthermia treatments for brain and prostate cancers, and novel medical imaging agents [19,20]. In many applications the degradation of the materials from magnetite to maghemite causes a loss of effective function due to the reduced magnetisation, while in the biomedical field there is considerable interest in the transformation between the two, given the different roles that ferrous (Fe 2+ ) and ferric (Fe 3+ ) ions play in the production of reactive oxygen species via the catalytic Haber-Weiss and Fenton chemistry pathways [21][22][23].…”
Section: Introductionmentioning
confidence: 99%